Pola Interaksi Sosial Komunitas Sunda Wiwitan Dalam Membangun Kerukunan Antar Umat Beragama - Hariyanto, Didik (POROS ONIM: Jurnal Sosial Keagamaan, 2022)
This study aims to identify patterns of social interaction by the Sunda Wiwitan community in realizing harmony between religious people in the people of Cigugur Village, Cigugur District, Kuningan Regency, West Java Province. Qualitative research in the form of case studies uses interpretive methods. Data collection through observation and interviews. Associative and dissociative patterns of social interaction became the theory of analysis. Data analysis includes presentation, reduction, and verification. The results showed the pattern of social interaction by the Sunda Wiwitan community in building harmony between religious people in Cigugur using associative interaction patterns. The existence of this associative intercation pattern in the realm of praxis is embodied through several strategies. First, build an attitude of religious tolerance. Second, build an attitude of openness (tepo seliro). Third, build cooperation between religious believers. Fourth, establish dialogue among religious people. The theoretical implications of research show that to build harmony in life in the midst of plurality of religious life requires a pattern of social interaction that is assioxiative. This research limitation has not examined the concrete role of the Cigugur regional government in the succession of religious harmony in the Sunda Wiwitan community.